ASAS PACTA SUNT SERVANDA DALAM PENEGAKAN HUKUM PIDANA INTERNASIONAL - Danel Aditia Situngkir (STIH Putri Maharaja, 2018)
The dark history of the first world war and the second world war had an impact increasingly increasing international attention to the protection of human rights. One of the efforts made was strengthening the provisions in international law. The state as the main actor in international relations plays an important role in the establishment of norms in international law. In its development, state relations are regulated in international agreements. The most common principle in international treaties is pacta sunt servanda. In general, the pacta sunt servanda defined by the state is only bound by the agreement pursuant approval from the state. This becomes very crucial for the protection of the sovereignty of the state. In reality, however, there are few international treaties that grant rights and obligations to countries that do not participate in international treaties. Related to international criminal law enforcement, the existence of this principle keep on debated, especially since those stipulated in international criminal law are international crimes and punishment of perpetrators of such crimes. The international dimension in a crime can be seen from various aspects. Therefore this paper will discuss the principle of pacta sunt servanda in law enforcement of international criminal law. This research was normative juridical as the main approach. The principle of pacta sunt servanda should not be based of state bondage in international criminal law enforcement, the state may be bound in that by customary international law.